Analysis of Efficiency and Change of Productivity in The Indonesian Banking Industry Using Data Envelopment Analysis (DEA) and Malmquist Total Factor Productivity - Heri Ispriyahadi; Raysa Trierdianto (Widya Cipta - Jurnal Sekretari dan Manajemen, 2020)
Abstract.This empirical study aims to identify differences in efficiency and productivity between state-owned banks, national foreign exchange private banks, and national non-foreign exchange private banks from 2010 – 2016. In the initial step, 43 banks listed on the Indonesia stock exchange were grouped into three groups. Then, we selected sampling using purposive sampling with the criteria of banks with an effective IPO date starts from 2010 onwards, and incomplete financial reports are excluded from sampling. The result was that 21 banks were selected as sampling and represented three bank groups. The research methods applied in this study were Data Envelope Analysis (DEA), Malmquist Total Productivity, and Paired Sample t-test. The outcomes suggest that: (1) national non-foreign exchange private banks have higher efficiency than two other bank groups, (2) change in the productivity of national foreign exchange private banks is powerfully vulnerable to the technological shift rather than changes in technical efficiency. The superiority of group national non-foreign exchange private banks was more efficient in reducing input costs such as labor costs and third-party funds. To cope with these problems, banks in Indonesia need to prompt innovations and advanced technology to improve efficiency and productivity.  Keywords: Banks, Efficiency, Productivity, DEA, Malmquist Total Indeks, Paired t-test